1987
DOI: 10.1083/jcb.105.6.2723
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of morphologically distinct endosomes in mutant and wild-type Chinese hamster ovary cells.

Abstract: we have shown that there is rapid acidification of endosomal compartments to pH 6.3 by 3 min in wildtype Chinese hamster ovary (CHO) cells. In contrast, early acidification of endosomes is markedly reduced in the CHO mutants, DTF 1-5-4 and DTF 1-5-1. Since these CHO mutants are pleiotropically defective in endocytosis (Robbins, A. R., S. S. Peng, and J. L. Marshall. 1983. J. Cell Biol. 96:1064-1071; Robbins, A. R., C. Oliver, J. L. Bateman, S. S. Krag, C. J. Galloway, and I. Mellman. 1984. J. Cell Biol. 99" 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
71
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 40 publications
5
71
0
Order By: Relevance
“…One of the possible sites where the defect could occur is in the large, prelysosomal endosomes. However, when we measured the pH of large endosomes, as distinguished by light microscopy, we found that the mean pH was nearly the same in the mutants DTG 1-5-4 and DTF 1-5-1 as in the wild-type cells (32). This suggested that the defect might be at an earlier step in the endocytic pathway.…”
mentioning
confidence: 92%
“…One of the possible sites where the defect could occur is in the large, prelysosomal endosomes. However, when we measured the pH of large endosomes, as distinguished by light microscopy, we found that the mean pH was nearly the same in the mutants DTG 1-5-4 and DTF 1-5-1 as in the wild-type cells (32). This suggested that the defect might be at an earlier step in the endocytic pathway.…”
mentioning
confidence: 92%
“…This sorting is a rapid step (tu2 < 3 min), and as depicted in Fig. 1, takes place in acidic organelles called sorting endosomes (Yamashiro and Maxfield, 1987), having 1. Abbreviations used in this paper: ce2M, ce2-macroglobulin; C6-NBD-PC, C6-NBD-phosphatidylcholine; C6-NBD-SM, N-[N-(7-nitro-2,1,3-benzoxadiazol-4-yl)-~-aminohexanoyl]-sphingosylphosphorylcholine; CCD, chargedcouped device; Cy3-ct2M, Cy3-1abeled ce2M; DiO-LDL, 3,3tdioctadecyl -oxacarbocyanine-labeled LDL; DiI-LDL, 3,3'-dioctadecylindocarbocyanine-labeled LDL; HF-12, Hepes-buffered Hams F-12 medium; LDL, low density lipoprotein; LDL-R, LDL-receptor; Rh-Tf, rhodamine-labeled Tf; "If, transferrin; Tf-R, "IT receptor; Tx, Texas-red; Tx-Tf, Texas-redlabeled Tf.…”
mentioning
confidence: 99%
“…This sorting is a rapid step (tu2 < 3 min), and as depicted in Fig. 1, takes place in acidic organelles called sorting endosomes (Yamashiro and Maxfield, 1987), having…”
mentioning
confidence: 99%
“…Long HS glycosaminoglycans interact with the peptide better than the short chains at the pH values found in endosomal compartments (pH 5.0 -6.5, Ref. 20), which again may reflect that the size of the glycosaminoglycan influences the 35 S counts retained on the membrane. Alternatively, because of their length, the nascent HS chains may be able to form more stable complexes with A␤(1-40) at these pH values than the heparanase-degraded glycosaminoglycans.…”
Section: Cho Hs Binds A␤(1-40)-mentioning
confidence: 99%
“…Experiments by Snow et al (1) suggest that both interactions are necessary for the formation of fibrillar A␤-amyloid, since coinfusion of A␤ and HSPGs into rat brain produced deposits, whereas coinfusion of A␤ and HS glycosaminoglycans did not. This is somewhat surprising, since in vitro, HS chains alone can cause both A␤ and A␤(1-40) to aggregate (3), and heparin converts A␤ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) into macrofibers (2). It may be that in vivo, stabilization of the aggregates and decreased amyloid susceptibility to proteolysis require A␤ to interact with both the core protein and HS chains.…”
mentioning
confidence: 99%